Genetic variance, heritability and expected response from selection for dry bean (Phaseolus vulgaris L.) yield and its components - Nienhuis, James; Singh, Shree P. (International Center for Tropical Agriculture, 1988)
Genetic variance, heritability, and expected response from selection are useful in devising alternative methods and criteria of selection. The objectives of this study were to estimate these for seed yield and its components from 200 F2 populations involving 80 cultivars and lines of mostly small-seeded dry bush bean (Phaseolus vulgaris L.) of growth habits I, II, and III. Most of the parental cultivars were either extensively grown in or bred for Argentina, Brazil, Central America, Colombia, Cuba, and Mexico and all were crossed in eight sets of ten parents each in a Design II mating system. The F2 populations, without parents, were evaluated in the field in a replicates-in-sets design at two locations in Colombia in 1983. Estimates of additive genetic variance were significant for yield, pods/plant, seeds/pod, and seed weight. Interaction with environments was also significant. Values for nonadditive genetic variance were not significant for either yield or yield components. The estimates of narrow sense heritability, based on the F2 population mean, were 0.37 plus or minus 0.24 for yield, 0.39 plus or minus 0.25 for pod/plant, 0.59 plus or minus 0.14 for seed/pod, and 0.88 plus or minus 0.18 for seed weight. The expected direct response from selection of the top 20 percent of F2 populations for yield per se would result in a 5.8 percent increase in yield with a correlated response of 6.5 percent in seed weight. In contrast, the expected gain from direct selection for seed weight would result in a 12.8 percent increase in seed weight with a correlated gain of 6.8 percent for yield. Direct selection for pod/plant would decrease yield, seed/pod and seed weight, while direct selection for seed/pod-would reduce pod/plant and seed weight.